Analytical Evaluation Of Crosstalk In A WDM Network - Sim, Ngee Thiam (2002)
An analytical approach is proposed to evaluate crosstalk in WDM network and to address issues on optical cross connect(OXC). This research is important since crosstalk is one of the basic criteria that characterize the performance of WDM network. Crosstalk leads to power transfer from one channel to another. The effect of crosstalk in OXC on overall WDM network performance is being investigated.